Senergisitas perkembangan Kognitif dengan Perkembangan Afektif pada Mata pelajaran Matematika SDN 26 Dompu. - Astiati, Siska Dwi; Ilham, Ilham; Aidin, Aidin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The concept of cognitive and effective learning requires the existence of main principles such as active learning, meaning that students as learning subjects are the most important factor, students learn to actively learn independently. This study aims to (1) determine cognitive development in the subjects of SDN 26 Dompu, (2) determine affective development in Mathematics subjects at SDN 26 Dompu, (3) determine cognitive development with affective development in Mathematics subjects at SDN 26 Dompu. The method of collecting data obtained from the results of the instrument and documentation as a complement. The data analysis technique used descriptive statistical analysis. From the results of data analysis, the lowest cognitive score in mathematics was 60 so it was grouped into